Pathological Findings of the Lung at Neonatal Autopsy in Dr. Hasan Sadikin General Hospital Bandung Period 2016-2019 - Rania Azzahra Salsazayasya Parikesit; Nita Novita; Hermin Aminah Usman (Althea Medical Journal, 2021)
Background: Infanticide is a criminal act when a mother kills her child at or soon after birth. Considering whether a case has been decided as infanticide, determination of the life of the neonate at birth is imperative. Breath signs from macroscopic and microscopic approacesh and hydrostatic test are useful indicators. This study aimed to explore the lungs pathological findings at autopsy of neonates.Methods: This study was a retrospective descriptive observational study, using medical records of neonatal deaths in the Department of Forensics and Medicolegal Dr. Hasan Sadikin General Hospital, Bandung for the period 2016–2019. Total sampling method was used. Inclusion criteria were neonatal death with presumptive infanticide, had autopsied and microscopic examination as well as neonatal death without putrefaction. Data on macroscopic and microscopic findings as well as the hydrostatic test were presented.Result: In total, 12 of the 42 medical records with data on presumptive infanticide met the inclusion criteria. For macroscopic findings, 7 of the 12 samples had positive results, meaning the lungs had sign of breath. Meanwhile, in microscopic findings 8 of the 12 samples had positive results. For the hydrostatic test, 8 out of 12 samples had positive results. Of the 12 samples, there were four samples that had different results, at least on one variable. Conclusions: Most of the cases are matched with macroscopic, microscopic, and hydrostatic test, but some unmatched data are also found. In order to improve reliability, especially for legal purposes in infanticide, it is necessary to conduct all the examination.